'I just tell myself it's okay': U.S. women's narratives about sexual safety and how they assess risk for sexually-transmitted infections. Issue 3 (3rd July 2022) - Fahs, Breanne
ABSTRACT: While some researchers have studied the spread of sexually-transmitted infections and diseases (STIs and STDs), little attention has been paid to the subjective narratives of how women assess sexual safety and the possibility of contracting STIs when having sex with partners. This study analysed semi-structured interviews with twenty women from a diverse 2014 community sample collected in a large Southwestern U.S. city in order to examine how women assess safety and danger in partners with regard to their sexual health. I identified five themes in how women described assessing their risk for contracting an STI: 1) Avoidance and refusal to ask; 2) Intuiting safety or 'just feeling' they are STI-free; 3) Verbally asking and trusting their responses; 4) Checking for physical signs of STIs; 5) Asking that a partner get tested. Tensions about sexual health knowledge, entitlement to ask for proof of a partner's STI status, and the gendered power dimensions of sexual health and sexual risk-taking are discussed. Ultimately, women's overwhelming lack of effective measures to ensure their own sexual health and safety are put into conversation with discourses of sexual (dis)empowerment.